Durvalumab, with or without tremelimumab, plus platinum-etoposide in first-line treatment of extensive-stage small-cell lung cancer: 3-year overall survival update from CASPIAN - Paz-Ares, L; Chen, Y; Reinmuth, N; Hotta, K; Trukhin, D; Statsenko, G; Hochmair, M J; Özgüroğlu, M; Ji, J H; Garassino, M C; Voitko, O; Poltoratskiy, A; et al. (ESMO open, 2022)
BACKGROUND: In the phase III CASPIAN study, first-line durvalumab in combination with etoposide plus either cisplatin or carboplatin (EP) significantly improved overall survival (OS) versus EP alone in extensive-stage small-cell lung cancer (ES-SCLC). Durvalumab plus tremelimumab plus EP numerically improved OS versus EP, but did not reach statistical significance. Here we report updated OS in censored patients after median follow-up of >3 years. PATIENTS AND METHODS: 805 patients with treatment-naïve ES-SCLC were randomized 1 : 1 : 1 to durvalumab plus EP, durvalumab plus tremelimumab plus EP, or EP. The two primary endpoints were OS for durvalumab plus EP versus EP and for durvalumab plus tremelimumab plus EP versus EP. RESULTS: As of 22 March 2021 (median follow-up 39.4 months, 86% maturity), durvalumab plus EP continued to demonstrate improved OS versus EP: hazard ratio (HR) 0.71 [95% confidence interval (CI) 0.60-0.86; nominal P = 0.0003]; median OS was 12.9 versus 10.5 months, and 36-month OS rate was 17.6% versus 5.8%. Durvalumab plus tremelimumab plus EP continued to numerically improve OS versus EP: HR 0.81 (95% CI: 0.67-0.97; nominal P = 0.0200); median OS was 10.4 months, and 36-month OS rate was 15.3%. Twenty-seven and nineteen patients in the durvalumab plus EP and durvalumab plus tremelimumab plus EP arms, respectively, remained on durvalumab treatment at data cut-off. CONCLUSIONS: Three times more patients were estimated to be alive at 3 years when treated with durvalumab plus EP versus EP, with the majority still receiving durvalumab at data cut-off, further establishing durvalumab plus EP as first-line standard of care for ES-SCLC.
Keywords: extensive-stage SCLC; monoklonální protilátky; CASPIAN; nádory plic; Antibodies, Monoclonal; malobuněčný karcinom plic; Platinum; tremelimumab; Humans; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; Etoposide; etoposid; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; durvalumab; Small Cell Lung Carcinoma; platina; overall survival; Lung Neoplasms; lidé